Strutture architettoniche e restauri in Santa Giulia di Brescia: la cripta di San Salvatore - de Paoli, Massimo (Hortus Artium Medievalium, 2017)
Abstract The monastery of San Salvatore of Brescia, after the suppression of the late eighteenth century, was the scene of numerous interventions of functional adaptation that have profoundly changed the appearance and the destination of use. These works, which ended with the recent organization in the city’s Museum, allow you to not only understand the architectural evolution of the ancient monastic foundation but also the complex role that it has had in representing the construction of the city’s identity with the Unity of Italy. The contribution, which is part of a scientific research project directed by Gabriele Archetti, presents the first significant results on the nineteenth-century reconstruction of the crypt and on the structural work carried out in the basilica of San Salvatore. The parametric modeling of Santa Giulia complex is being built.